Pengembangan Karir Karyawan Perbankan di Kota Makassar - Mahlia Muis (Conference In Business, Accounting, And Management (CBAM), 2012)
This research aims to find out whether there are any differences in promotion based on age, education, working period, sex, marital status, number of responsibilities, horizontal move, and number of appreciations given to employees at banks in Makassar City. The results show that education, sex and number of rewards have a significant influence based on odd ratio of each variable. On the other hand, age, working period, marital status, number of dependants, and horizontal move do not have a significant influence on the career development of banking employees in Makassar City, which are measured based on the promotion received since they worked as bank employees.Key words: age, working period, marital status, number of dependants, horizontal move, career development.